An Alternative Method to Create Highly Transparent Hollow Models for Flow Visualization. Issue 2 (February 2013) - Stoiber, Martin; Schlöglhofer, Thomas; Aigner, Philipp; Grasl, Christian; Schima, Heinrich
Aim: Transparent hollow models are needed to visualize and quantify flow in various applications. To obtain the final transparent model, an intermediate molding of the fluid space with an easily removable material is required. Currently used materials to produce this intermediate molding have limitations: toxicity, cost, and a tendency to penetrate the final model, thereby degrading its transparency. In this work an alternative method is presented using chocolate as the fluid-space molding material. Methods: Starting from a three-dimensional computer aided design (CAD) geometry, a fluid space model of a human aorta was produced out of chocolate. The replica was coated and cast in a block of highly transparent silicone (Sylgard184; Dow-Corning, Midland, MI, USA). After the silicone was cured, the chocolate was removed using hot water. The geometric accuracy of the fluid-space mold and the transparency of the final model were investigated. Results: The mean divergence of the chocolate fluid-space mold from the original geometry was 5.7%. The silicone casting had no defects and perfect transparency for particle tracking. Fluid boundaries were invisible when tested with a fluid whose refractive index matched silicone. Conclusions: The process we describe is a cheap and effective way to create transparent models that have excellent optical quality.